Impact of Digital Transformation on The Level of Economic Security - AGNIESZKA SAŁEK-IMIŃSKA; WITOLD IMIŃSKI (Communications of International Proceedings, 2024)
The authors of this paper aim to assess the impact of digital transformation on the economic security of enterprises. To achieve this, a research problem was formulated, which seeks to answer researchers' pressing questions: Is there a relationship between digital transformation and the level of economic security of enterprises? Does RPA contribute to streamlining the digital transformation process in the enterprise and thus contribute to its development and improvement of competitive position, thereby affecting its economic security? There is a lack of research in the subject literature regarding the specific impact of digital transformation, including RPA, on the economic security level of enterprises. There is a need to understand this relationship and identify key areas of digital transformation's impact on economic security. To achieve the research objectives, a qualitative approach based on a case study was employed. Semi-structured interviews were conducted with experts employed in the subject of the study, using an interview questionnaire as a research tool. The study confirmed the existence of a relationship between digital transformation and the economic security of enterprises. Key areas of digital transformation's impact on economic security include strategy, technological capabilities, human resources, customer communication, and information security. The results indicate an improvement in customer service quality, increased productivity, reduced error risk, cost reduction, and improved information processing security as effects of digital transformation. Additionally, the study confirmed that RPA contributes to streamlining the digital transformation process and improving the competitive position of the enterprise by implementing new tools supporting the achievement of strategic, tactical, and operational goals, particularly in cost reduction.
Keywords: digital transformation; economic security; robotic process automation